Influence of friction on gear dynamics - Paulo Fernandes (2006)
Sliding friction between meshing teeth can be a very important of noise and vibration excitation source in geared systems. This study presents a single degree of freedom torsional model for a FZG type C single gear pair. Starting from a base dynamic model with time varying mesh stiffness as the only internal excitation, the influence of additional effects is gradually considered, namely, constant friction coefficients and time varying output torques. In particular, sliding friction is modeled as external and internal linear time varying excitation. On the other hand, time varying output torques are also considered as alternative of constant driven torque. The gears rotational vibrations are calculated by Runge-Kutta method for different combinations of rational speeds, input torques and friction coefficients. The results indicate that dynamic transmission errors calculated from modeling the friction force as external and internal excitation are quite different, especially when contact point moves ahead of pitch point. However the influence of time variations on output torque is very reduced.